Augmented Reality and Virtual Reality Displays: Perspectives and Challenges - Zhan, Tao; Yin, Kun; Xiong, Jianghao; He, Ziqian; Wu, Shin-Tson (iScience, 2020)
As one of the most promising candidates for next-generation mobile platform, augmented reality (AR) and virtual reality (VR) have potential to revolutionize the ways we perceive and interact with various digital information. In the meantime, recent advances in display and optical technologies, together with the rapidly developing digital processers, offer new development directions to advancing the near-eye display systems further. In this perspective paper, we start by analyzing the optical requirements in near-eye displays poised by the human visual system and then compare it against the specifications of state-of-the-art devices, which reasonably shows the main challenges in near-eye displays at the present stage. Afterward, potential solutions to address these challenges in both AR and VR displays are presented case by case, including the most recent optical research and development, which are already or have the potential to be industrialized for extended reality displays. [Display omitted] •Introduce augmented reality (AR) and virtual reality (VR) and their applications•Analyze the challenges in AR and VR displays•Potential solutions to address challenges in both AR/VR displays are presented Optical Imaging; Photonics; Laser; Optical Materials